"Future Prospects f o r U.S. Mining" . - Simon D. Strauss (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
What are future prospects for U.S. mining? In many quarters the assumption is made that this country has passed its zenith as a mineral producer -- that it is in a period of decline and that it is becoming a have-not nation like Japan and much of Western Europe. These industrial rivals of ours must depend almost entirely on others for their mineral supplies. In trying to answer this question one must of course distinguish between resources and productive capacity. In today's volatile and competitive markets, the definition of what are reserves and what are merely identified resources becomes ever more difficult. Many large deposits have been found that are unlikely to be viable in the marketplace under normal conditions but that can be of significance to the nation's military and industrial security in times of emergency. I should like to draw on personal experience from World War I1 for illustration. 4fter Pearl Harbor great concern developed over the availability of a long 1ist of strategic materials for which this country was largely dependent on imports. Included were a number of minerals of which domestic deposits had been identified. Among these were chromite, manganese ore, mercury, mica and tungsten.